The Main Topics at the Oncoplastic Breast Surgery Course and Expert Panel - GÜLLÜOĞLU, MAHMUT BAHADIR (AVES, 2017)
The Oncoplastic and Reconstructive Breast Surgery course was held in Izmir by the Izmir Breast Diseases Federation in collaboration with the Breast Diseases Federation of Turkey. The techniques of oncoplasty, the application details and experience in this subject were shared. In this text, the main topics and outcomes are briefly summarised. These evaluations can be considered highly valuable on both local and regional scales.
Keywords: Oncoplastic breast surgery; quadrantectomy (surgery for breast cancer based on tumour location); breast surgery